1999
DOI: 10.1063/1.478621
|View full text |Cite
|
Sign up to set email alerts
|

The ethylene 1 1B1u V state revisited

Abstract: We describe a general procedure to resolve the problem of artifical valence/Rydberg mixing encountered in ab initio CI calculations on the V (1 1B1u) state of ethylene. Davidson and McMurchie realized that the key to this problem are orbitals which adequately represent the V state. A two-step procedure is proposed, in which the first step focuses on generating appropriate molecular orbitals and the second step aims to describe the electron correlation quantitatively. A series of the currently most extensive MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
116
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(142 citation statements)
references
References 29 publications
21
116
0
1
Order By: Relevance
“…19 The accuracy of the CASPT2 data also should be checked in critical regions of the PE surface by more accurate MRCI calculations. 8 Finally, nonadiabatic couplings with low-lying Rydbergs states, especially the 3s Rydberg state, may play a role for the radiationless decay dynamics of the V state ͑the Rydberg states have also been omitted, however, in the recent directdynamics simulations 30,32 ͒. Clearly, more comprehensive and more accurate electronic-structure and dynamics calculations are required for a complete understanding of the photochemistry of the carbon-carbon double bond.…”
Section: Discussionmentioning
confidence: 99%
“…19 The accuracy of the CASPT2 data also should be checked in critical regions of the PE surface by more accurate MRCI calculations. 8 Finally, nonadiabatic couplings with low-lying Rydbergs states, especially the 3s Rydberg state, may play a role for the radiationless decay dynamics of the V state ͑the Rydberg states have also been omitted, however, in the recent directdynamics simulations 30,32 ͒. Clearly, more comprehensive and more accurate electronic-structure and dynamics calculations are required for a complete understanding of the photochemistry of the carbon-carbon double bond.…”
Section: Discussionmentioning
confidence: 99%
“…The MRMP 9 and CC 12 results can therefore be explained in the same context. Müller et al 45 recently showed that a complete removal of the valence-Rydberg mixing problems was not possible even for the most accurate correlation methods such as MS-CASPT2, multireference-singles and doubles configuration interaction ͑MR-SDCI͒, multireference quadratic coupled-cluster ͑MR-AQCC͒, or equation of motion-coupled-cluster ͑EOM-CC͒ in ethene unless the reference wave function is corrected including dynamical correlation effects. We find that MS-CASPT2 can remove most of the mixing 25 and provide good excitation energies, but in severe valence-Rydberg situations the PMCAS-CI properties can be largely perturbed by the mixing.…”
Section: Valence-rydberg Mixing In the 1 B 2 States Of Pyrrolementioning
confidence: 99%
“…27 The exponent of this orbital was set to 0.0208 (in atomic units), which was determined by fitting the energy of the π-3s Rydberg [Ryd(3s) in Mulliken notation] state at the FranckÀCondon (FC) and Ryd(3s)/ππ* intersection geometries to previous computational and experimental results. 18,20,24,43,44 Details of the fitting procedure are provided in Supporting Information. The CASSCF active space consisted of three orbitals (π, π*, and 3s) with two electrons.…”
Section: Computational Detailsmentioning
confidence: 99%